Between empire and nation state. Urban space and conflicting memories in Trieste (19th–early 20th century) - Griffante, Andrea (Journal of Architecture and Urbanism, 2015)
Cities are particular spaces in which such a fight for territory occurs. By their own nature, cities imply a work of transformation and appropriation of territory into a narrative construct or text. In the 19th and early 20thcentury, Trieste underwent a transformation of its own urban space that expressed the existence and concurrence of different national narratives. In the 18th and 19th centuries the Trieste’s coastline performed the cosmopolitan elite’s identity by highlighting the relation between social status, ethnic origins of elite’s member, and the individuals’ conscience of participating in the exceptionality of a city ‘without history.’ As the elite’s economic ground changed, the representation of identity in space changed consequently. The consolidation of fascist regime supported the construction of a new myth of Trieste characterized by an old Roman origin and the heroic efforts of its inhabitants to join the ‘Motherland’ that led to the creation of a new main urban axis constellated with sites highly representative of Trieste’s ‘Latinity’ and permeated by a sense of collective participation in historical continuity.